Information Science (IS) and It’s Increasing Interaction with Electronic Science and Mechanical Sciences - Paul, Prantosh Kumar; Shivraj, K. S. (Asian Journal of Electrical Sciences, 2013)
Information Science plays an important role in the field of applied science and technology. Information Science is truly responsible for several societal improvements like for removing information and digital divide, for improved Information society, creation of information based knowledge Economy and so on [9]. Information Science is mistakenly considered as Computer Science branch or Library Science field but it is totally different and interdisciplinary subject responsible for Information Transfer Cycle. Information Science has two foci manual and computational. The computational Information Science has several connection and relationship with the world of electronics and Electrical Science. In this paper we describe the interaction and interconnection in between the Information Science and with technology which mainly depends on Electronics and Electrical Science Emphasizing the contemporary scenario [10, 13].